Flow and heat transfer augmentation using helical coiled wire of different cross-sections - Hanoon, Murtadha; Fagr, Mohsen; Mekki, Kamaal (Al-Qadisiyah journal for engineering science, 2025)
In this numerical investigation, the effectiveness of utilizing advanced helical coiled wires (HCWs) as tube inserts for the purpose of heat transfer and turbulence enhancement under turbulent flow conditions (Reynolds numbers: 3000-11000) was examined. HCW followed a helical guide path instead of a straight one in a typical coiled wire case, resulting in increased flow complexity. Circular and equilateral triangular wires, maintaining equal cross-sectional areas, were tested, with pitch ratios (P/D) being 1, 1.5, and 2. Simulation was performed using ANSYS Fluent 22, the working fluid considered throughout the study was air. Results indicated increased Nusselt number (Nu) and friction factor (f) compared to a plain tube. The thermal performance factor was found to have an inverse relationship with both pitch ratio and Reynolds number severally. The study reported that the circular insert at (P/D) = 1 and Re = 3000 exhibited the maximum thermal performance factor of 1.379, while the highest enhancement ratio for the Nusselt number of 4.14 was recorded in the case of the triangular insert at the same Reynolds number. Additionally, the maximum friction factor increase occurred with the triangular model at Re = 11000, reaching a friction factor ratio of 40.4.